Artificial neural network model for prediction of dynamical behavior in spray boom - Abd. Rahman, Roslan (2012)
Spray booms are usually used in farming to broadcast pesticide and chemicals. Nowadays, the widths of sprayers are increasing permanently due to increase in the width of farm yards. This issue leads to unwanted vibration in sprayer, causing overdoses or under-doses on the field. In active vibration control of sprayers, a model to predict the dynamical behavior of sprayer is necessary. In this study, a novel method is presented to predict dynamic behavior in spray boom by using artificial neural network modeling.